PERSEPSI MAHASISWA TERHADAP PELAKSANAAN PEMBELAJARAN DARING PADA MASA PANDEMI COVID- 19 DI STKIP PESISIR SELATAN - Muhammad Arif; Dina Syaflita (Sosio-Didaktika: Social Science Education Journal, 2021)
The purpose of this study was to determine student perceptions regarding the process of implementing online lectures during the pandemic at STKIP Pesisir Selatan as a material for consideration in the implementation of subsequent online lectures. This research is a qualitative descriptive research. The research instruments used were interview sheets to lecturers and questionnaires filled out by students. The data analysis technique used is descriptive analysis technique. The results of this study indicate that most of the lectures at STKIP Pesisir Selatan are conducted synchronously via googlemeets and zoom. The use of whatsapp and email is more intended in providing lecture explanations and sending assignments. In general, adjustments to teaching materials have been made but it is necessary to evaluate and improve the function of lecturers who have changed due to this change in learning modes. Problems with the quality of the internet network and the availability of quotas are the main constraining factors for the implementation of online lectures at STKIP Pesisir Selatan in particular. This affects the effectiveness of learning as a result students find it difficult to understand the material in this online learning. In terms of sustainability in the next semester, most students do not agree with the implementation of online learning to be continued in the next semester.